Pemberdayaan Kader Dalam Upaya Pencegahan Dan Penanggulangan Anemia Pada Ibu Hamil Di Desa Telaga Piru - Harmiyati Harmiyati; Dewi Susanti; Sufiani Sufiani (Jurnal Pengabmas Masyarakat Sehat, 2021)
Anemia that occurs in some pregnant women is caused by an increase in the need for nutrients and changes in the blood during pregnancy. Anemia will have a bad effect on the health of the mother and the fetus, that is, this condition will increase the morbidity and mortality of mother and child. Maternal mortality rate (MMR) in Ambon city, in 2013 there were 4 maternal deaths or 28.6 per 100,000 live births. In 2014 there were 2 mothers or 59.9 per 100,000 live births and in 2015 there was an increase of 5 or 36.3 per 100,000 live births. The main cause of death is bleeding because anemia is not handled. Efforts to prevent and overcome iron nutritional anemia through the provision of iron supplements are prioritized for pregnant women. Therefore, to prevent nutritional anemia in pregnant women, iron supplementation with a daily dose of 1 tablet (60 mg elemental iron and 0.25 g folic acid) consecutively for at least 90 days during pregnancy.Keywords: anemia in pregnancy, prevention, and control of anemia.